Observing the Development of the As-Sunnah Islamic College: (Historical Studies) - Isnawati; Nunzairina; Muhammad Sapii Harahap (WARAQAT : Jurnal Ilmu-Ilmu Keislaman, 2022)
The formulation of the problem in this research is how is the development of the As-Sunnah Islamic High School from 2002 to April 2022?” The purpose of this study is "to find out and explain the history of the development of STAI As-Sunnah from 2002 to April 2022. The research method used is to use a historical qualitative method, namely by a logical analysis of events that took place in the past. This research is that in 2002 the Ar-Risalah Al-Khairiyah Foundation was established as a legal umbrella for educational institutions. The initial education is at D3 Da'wah As-Sunnah Academy. Then it was changed to Ma'had Aly As-Sunnah then right in 2012 it officially became STAI As-Sunnah. And it will be planned to become an Institute level, towards that plan in 2021 it is available and has received operational permits for 3 Faculties and 6 Study Programs, then the alumni are qualified as evidenced by the results of the exam and the mandatory thesis trial requirements, namely the obligation to pass the 7 zuz Qur'an exam and pass the language. Arabs, then the alumni can immediately get employment as evidenced by the letter of assignment obtained by the alumni.